The thin red line [videorecording (DVD)] - Malick, Terrence, 1943-; Malick, Terrence, 1943-; Penn, Sean, 1960-; Brody, Adrien; Caviezel, Jim, 1968-; Chaplin, Ben; Clooney, George; Cusack, John, 1966-; Harrelson, Woody; Koteas, Elias, 1961-; Leto, Jared, 1971-; Nelson, Tim Blake; et al. (Twentieth Century Fox Home Entertainment, 2001)
In World War II, the outcome of the battle of Guadalcanal will strongly influence the Japanese's advance into the Pacific. This is the story of Charlie Company's landing and battle experience there in 1942. The story concentrates on how the battle affects, and is effected by, Commanding officer Lt. Col. Gordon Tall, Captain James Staros, Sgt. Edward Welsh, and two privates, Witt and Bell. Charlie Company is attacking a seemingly impregnable position, and the men just face the terror and chaos of war.